933. Serum Albumin Is Associated With Higher Inflammation and Carotid Atherosclerosis in Treated HIV Infection. (26th November 2018) - Dirajlal-Fargo, Sahera; Kulkarni, Manjusha; Sattar, Abdus; Funderburg, Nicholas; McComsey, Grace A
Abstract: Background: Lower serum albumin has recently been associated with cardiovascular disease and non-AIDS malignancies in HIV. This analysis explores the associations between serum albumin and markers of inflammation and atherosclerosis. Methods: We conducted a nested study within in the SATURN-HIV trial in which 147 HIV+ adults on stable antiretroviral therapy (ART), were virally suppressed, and had an LDL-cholesterol level <130 mg/dL were randomized to 10 mg daily rosuvastatin or placebo. Measures of serum albumin, carotid intima media thickness (IMT, surrogate marker of atherosclerosis), inflammation, T-cell and monocyte immune activation were assessed at baseline, 24, 48, and 96 weeks later. Spearman correlations and linear-mixed effects models with random intercept and slope were conducted to assess associations with albumin. Results: Mean age was 45 years, 80% were male, 69% were African American, and 46% were receiving protease inhibitors. Mean serum albumin was not significantly different between the groups at any time points (4.05–4.08 g/dL in statin arm vs. 4.01–4.11 g/dL in placebo arm, P = 0.08–0.35). Low serum albumin significantly correlated with elevated levels of interleukin-6 (IL6), d-dimer, fibrinogen, and high sensitivity C-reactive protein (hsCRP) at all time points ( P ≤ 0.04). Low serum albumin also correlated with higher inflammatory monocytes (CD14+CD16+) at week 24 and week 96 ( P ≤ 0.03) but not with markers of T-cell activation at any time point ( P ≥ 0.10). Lower baseline albumin significantly predicted larger changes in IMT ( P = 0.03), IL6, d-dimer, tumor necrosis factor-α receptor 1, fibrinogen, and hsCRP ( P ≤ 0.02) over 96 weeks. After adjusting for age, gender, smoking, body mass index, vascular cell adhesion molecule and creatinine clearance, every 1 g/dL decrease in albumin remained associated with a 0.5 mm increase in IMT over 96 weeks ( P = 0.05). Conclusion: Lower serum albumin in controlled HIV is associated with higher markers of chronic inflammation, hypercoagulation, and monocyte activation, which could explain the prior observation that albumin predicts non-AIDS events in HIV. Our findings suggest that serum albumin may predict progression of carotid atherosclerosis independent of traditional risk factors. Disclosures: G. A McComsey, Gilead: Consultant, Consulting fee and Research support. Merck: Consultant, Consulting fee and Research support. Viiv: Consultant, Consulting fee and Research support. Roche: Research Contractor, Research support. Astellas: Research Contractor, Research support.